Classifying social enterprises with organizational culture, network and socioeconomic performance: Latent profile analysis approach - Changhwan Shin; Jungkyu Park (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
Culture is a key driving force in enhancing organizational performance. The results of recent studies indicate the importance of managers having the capacity to understand organizational culture and link it to organizational performance improvement. This study aims to examine the relationship between organizational culture and performance improvement in social enterprises. In the past, organizational culture was described in terms of a single dimension, but it is now understood that different cultures reflect different values and beliefs, in a seemingly contradictory manner, and can coexist within any given organization. We analyze the relationships among social enterprise networking, performance, and organizational culture, using the four organizational culture classifications of the competing values framework, which reflects recent perspectives. A survey was conducted among 100 social entrepreneurs, and latent profile analysis was applied to the data. The analytical results identify four latent profiles-namely, strong-balanced, weak-balanced, hierarchical, and group-dominant-and show that a balanced culture fosters high-level socioeconomic performance.
Keywords: 650; organizational culture; networking; competing value framework; latent profile analysis; social enterprise; performance